1970
DOI: 10.1104/pp.45.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age and Illumination on Distribution of Several Calvin Cycle Enzymes in Greening Barley Leaves

Abstract: Activities of phosphoriboisomerase, phosphoribulokinase, and ribulose 1,5-diphosphate carboxylase, protein content, and chlorophyll accumulation in dark-grown barley seedlings were measured before and after illumination. Enzymatic activities, levels of soluble protein, and accumulation (upon illumination) of chlorophyll in leaves declined from tips toward the base. In response to increasing time of illumination, chlorophyll accumulation and activities of phosphoribulokinase and ribulose 1 ,5-diphosphate carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Thereafter the protein remains constant, presumably as the chloroplast development has been completed. Obendorf and Huffaker (1970) have suggested that this phenomenon may be related not only to the manner in which monocotyledonous plants develop, but also to the availibility of substrates during development. They pointed out that availibility of an energy source for a longer time could allow greater physiological development in leaf tips than in the basal sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter the protein remains constant, presumably as the chloroplast development has been completed. Obendorf and Huffaker (1970) have suggested that this phenomenon may be related not only to the manner in which monocotyledonous plants develop, but also to the availibility of substrates during development. They pointed out that availibility of an energy source for a longer time could allow greater physiological development in leaf tips than in the basal sections.…”
Section: Resultsmentioning
confidence: 99%
“…They pointed out that availibility of an energy source for a longer time could allow greater physiological development in leaf tips than in the basal sections. The basal section of barley appears to contain appreciable amounts of not only chloroplastic PGK, but also LHCP and Rubisco (Obendorf and Huffaker 1970;Viro and Kloppstech 1980), even though there is no photosynthetic CO2 fixation (Baker and Leech 1977). It is not clear if Rubisco is active in this region or whether the oxygenase activity appears first.…”
Section: Resultsmentioning
confidence: 99%
“…However, when barley seedlings are grown in the dark for >5 d, chlorophyll accumulation upon light exposure rapidly decreases with increasing pregrowth in the dark (Obendorf and Huffaker, 1970). A reversal of the basipedal gradient of chlorophyll accumulation is also observed in these seedlings, suggesting that the more mature tissues of these leaves are beginning to undergo programmed senescence (Obendorf and Huffaker, 1970).…”
Section: Discussionmentioning
confidence: 93%
“…Transfer of these seedlings to the light causes a rapid synthesis of chlorophyll and plastid maturation that again follows a basipedal gradient, such that within 48 h these seedlings contain chlorophyll amounts similar to light-grown plants (Robertson and Laetsch, 1974). However, when barley seedlings are grown in the dark for >5 d, chlorophyll accumulation upon light exposure rapidly decreases with increasing pregrowth in the dark (Obendorf and Huffaker, 1970). A reversal of the basipedal gradient of chlorophyll accumulation is also observed in these seedlings, suggesting that the more mature tissues of these leaves are beginning to undergo programmed senescence (Obendorf and Huffaker, 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation